2010
DOI: 10.1002/ldr.1050
|View full text |Cite
|
Sign up to set email alerts
|

The vegetation cover dynamics (1982–2006) in different erosion regions of the Yellow River Basin, China

Abstract: Vegetation significantly influences human health in the Yellow River basin and the plant cover is vulnerable to people. Typical types of erosion in the Yellow River basin include that caused by water, wind and freeze-thaw. In this paper, vegetation cover change from 1982 to 2006 was studied for a number of different erosion regions. The Global Inventory Monitoring and Modeling Studies Normalized Difference Vegetation Index (GIMMS NDVI) data were employed, while climatic data were also used for analysis of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 38 publications
4
71
0
1
Order By: Relevance
“…This relationship was evident within a season and in the previous seasons (Fig. 4) probably because the main vegetation type in the semi-humid region is cropland, which is mainly on relatively flat terrain where human interference (e.g., irrigation) is common; thus, crop growth seldom depends on precipitation (Miao et al 2012). Temperature could thus be the limiting factor for vegetation growth.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This relationship was evident within a season and in the previous seasons (Fig. 4) probably because the main vegetation type in the semi-humid region is cropland, which is mainly on relatively flat terrain where human interference (e.g., irrigation) is common; thus, crop growth seldom depends on precipitation (Miao et al 2012). Temperature could thus be the limiting factor for vegetation growth.…”
Section: Discussionmentioning
confidence: 91%
“…Zhang et al (2006) showed that water and temperature on the plateau are important along both latitudinal and longitudinal gradients. Vegetation growth trends have changed significantly in many parts of the plateau over the last three decades (Miao et al 2012;Xin et al 2008); thus, understanding the responses of vegetation growth to climatic changes is critical and so is predicting the future interactions between the terrestrial ecosystems and the climate system in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Annual precipitation distribution and Vegetation coverage are taken as the representations of the group of Natural Environment, which usually play important roles in landslide occurrence [42,43].…”
Section: In Natural Environment Groupmentioning
confidence: 99%
“…Several experiments in the middle reaches of the Yellow River basin show that reforestation can reduce surface runoff by 30.8-75.1%, and grass plantingby 17.2-58.9% (Xu and Niu 2000). The vegetation cover in the Yellow River basin (expressed as NDVI) increased by the rate of 0.075% per year from 1982 to 2006 (Miao et al 2012), due to the "Grain for Green (GFG)" programme, and it has increased further since 1999.…”
Section: Discussionmentioning
confidence: 99%